135k views
3 votes
Find (f o f)(0). f(x) = 3x - 2

User Giao
by
5.7k points

2 Answers

3 votes

(f o f)(0) = f(f(0))

f(0) = 3(0) - 2 = -2

so

f(f(0)) = 3(-2) - 2 = -6 - 2 = -8

Answer

(f o f)(0) = -8

User Hanako
by
5.5k points
6 votes

Answer:

(f o f)(0) = -8

Explanation:

The given function is
f(x)=3x-2

Let us find the composite function (fof)(x)


(fof)(x)=f(f(x)\\\\=3(3x-2)-2\\\\=9x-6-2\\\\=9x-8

Now, substituting, x = 0 in this composite function to find (f o f)(0)


(fof)(0)=9(0)-8\\\\0-8\\\\=-8

Thus, we have

(f o f)(0) = -8

User Vitro
by
7.0k points